Comparative study of two adult asthma education programs in enhancing self-care behavior and symptom control - Tuazon, Josefina Angeles (1999)
Asthma is an increasing concern in the Philippines with an estimated prevalence of up to 16
The enabling factor, inhaler technique, of both regular and enriched groups had significant positive change towards perfect inhaler technique compared to no change in the control group.
Thesis (DrPH Health Promotion and Education)--University of the Philippines, Manila
Keywords: Asthma education